Practical Neurology DVD Review. - Biller, José (Wolters Kluwer Health, 2005)
Featuring 102 video clips of patients with diverse neurologic problems, this text/DVD package is a powerful educational tool for mastering the clinical practice of neurologic diagnosis. Through real-time videos of comprehensive neurologic examinations, the authors demonstrate the techniques and reasoning that lead to accurate diagnosis. Each case begins with a patient history or vignette and then shows the neurologic examination, the signs and symptoms elicited, and photos from imaging or other studies. Concise text describes the examination, the findings, and the diagnosis. Also included are.